A Quantitative Analysis of Knowledge Collaboration Enablers for Practicing Engineers. Issue 3 (3rd July 2021) - Wong, Silky S. K.; Cross, Jennifer A.; Burton, Cherise M.
Abstract: Transferring knowledge from experts to apprentices is critical for sustaining a company's competitive advantage. Further, existing literature indicates that employees in the Millennial (Y) generation and Generation Z prefer collaboration in the work environment. To address such needs, this research study aims to analyze the factors that enable knowledge collaboration among apprentices and experts in the practice of engineering. Survey data collected from 138 apprentices in the practice of engineering revealed that apprentices are more likely to collaborate with experts within their companies when they can trust the experts and perceive support for collaboration from senior management. This research adds to the body of knowledge by explicitly addressing apprentices' trust, senior management support, intrinsic motivation, and knowledge collaboration with experts. Engineering managers can use this article to utilize trust, support from senior management, and employee's intrinsic motivation to increase knowledge collaboration success among engineering experts and apprentices.